2021
DOI: 10.3389/fimmu.2021.768098
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Evo–Dev: A Theory of Inflammation-Induced Oncogenesis

Abstract: Chronic inflammation is a prerequisite for the development of cancers. Here, we present the framework of a novel theory termed as Cancer Evolution-Development (Cancer Evo-Dev) based on the current understanding of inflammation-related carcinogenesis, especially hepatocarcinogenesis induced by chronic infection with hepatitis B virus. The interaction between genetic predispositions and environmental exposures, such as viral infection, maintains chronic non-resolving inflammation. Pollution, metabolic syndrome, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 127 publications
(164 reference statements)
0
17
0
1
Order By: Relevance
“…Telomeres are repetitive DNA sequences located at the ends of the chromosomes and intact telomeres are essential for genomic integrity and the maintenance of the cellular proliferative potential ( 36 ). Inflammation and telomere shortening are hallmarks of the early stages of chronic liver disease and play a pivotal role in the early onset of neoplasia ( 37 , 38 ). In a previous study, we found that low telomere length is associated with a higher risk of tumor onset ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Telomeres are repetitive DNA sequences located at the ends of the chromosomes and intact telomeres are essential for genomic integrity and the maintenance of the cellular proliferative potential ( 36 ). Inflammation and telomere shortening are hallmarks of the early stages of chronic liver disease and play a pivotal role in the early onset of neoplasia ( 37 , 38 ). In a previous study, we found that low telomere length is associated with a higher risk of tumor onset ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the peptides excreted by adipocytes and/or myocytes have pro-inflammatory proprieties (leptin, resistin, chemerin, vaspin, RBP-4 [ 202 ]) or anti-inflammatory proprieties (adiponectin, omentin, vaspin and irisin [ 202 , 214 ]). Cancer development and evolution may depend on chronic inflammation [ 215 ]; thus, an imbalance in the pro-inflammatory and anti-inflammatory effects of adipokines/adipomyokines may also be one of the factors influencing cancer development.…”
Section: Final Remarks and Conclusionmentioning
confidence: 99%
“…This activity leaves signatures along the double helix that are clearly traceable to A3 family members and are found predominantly in cancer cells [73]. As the structural details of A3s interaction with nucleic acids are being unveiled [74], the ambivalent effect of these protective enzymes is also being highlighted, as an elevated expression of APOBEC3s may provide a reason for aberrant cancer-inducing somatic mutations in human papilloma virus (HPV) [75][76][77] and HBV [78] infections, as well as an extensive range of other tumor types [73,79,80], even in the context of inflammation [81].…”
Section: Overview Of Apobec3 Functionsmentioning
confidence: 99%